Nutrient digestibility and rumen fermentation of dried cassava peels and brewers dried grains based diets by West African Dwarf (WAD) sheep (2013)
In the tropics, supplementing concentrates with grasses, especially during the dry season could improve protein to energy ratio in ruminants thereby improving optimum production. Also, supplementation with a protein source enhances the production capacity of ruminants. Therefore, this study was designed to determine the nutrient digestibility and rumen fermentation kinetics of Panicum maximum supplemented with brewers dried grains and dried cassava peels based diets by West African Dwarf (WAD) lambs. Nine lambs of about 9 months in age and bodyweight ranging from 10.5kg-16.5kg were randomly divided into 3 groups and assigned to the following diets: Diet 1-100% Panicum maximum, Diet 2 - 81% DCP + 13.50% PKC + 2% Oyster shell + 2% Salt + 1.50% Premix and Diet 3-81% BDG + 13.50% PKC + 2% Oyster shell + 2% Salt and 1.50 Premix. Result showed that animals on diet I recorded the least significant (p< 0.05) dry matter digestibility (55.00%) to those on diets 2 and diet 3. Animals on diet 3 recorded the best crude protein digestibility (66.88%) which was significantly different (p<0.05) from those on diets 1 and 2 (53.04% and 56.79%). Animals on diet 1 recorded the highest significant (p<.0.05) amount of ammonia nitrogen at O and 4 hours post feeding. The same trend seems to occur for volatile fatty acids (acetate, propionate and butyrate) at O hour post feeding. However, at 4 hour post feeding, animals on diet 3 recorded a slight numerical advantage over other animals. It can therefore be deduced from this study that diet 3 was most preferred as evident from the Chemical composition of the feed and nutrient digestibility of the lambs.